Seismic Rehabilitation of RC Columns Under Biaxial Loading: An Experimental Characterization. (August 2015) - Rodrigues, Hugo; Arêde, António; Furtado, André; Rocha, Patrício
Abstract: The main purpose of this paper is to present an experimental campaign of different strategies for seismic repair and retrofit of RC columns previously subjected to biaxial cyclic loading actions and evaluate the benefits concerning their structural behaviour when again subjected to biaxial cyclic loading. Column rehabilitation was performed in order to improve the ductility and/or strength characteristics and it was obtained through increasing the concrete ductility conditions, with efficient jacketing, or increasing the amount of longitudinal and transversal steel. The aim is, therefore, to contribute in developing and calibrating a procedure that enables the evaluation of the efficiency of different retrofit solutions, their possibilities and fields of application. The results are presented in terms of shear-drift, stiffness degradation, ductility and energy dissipation. The retrofitted results will be compared with the results of the original one, deducting about the structural efficiency by each type of retrofit technique adopted.